2018
DOI: 10.1002/slct.201803668
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Influence on Structural Properties and Reactivity of Bis(μ‐oxo)dimanganese(III,IV) Species and Comparison of Reactivity with Terminal MnIV‐oxo Complexes

Abstract: The ligand influence on structure and reactivity of a pair of bis (μ-oxo)dimanganese(III,IV) complexes was investigated. The pentadentate N4py and DMM N4py ligands were employed to assemble the [Mn III Mn IV (μ-O) 2 (N4py) 2 ] 3 + (1) and [Mn III Mn IV (μ-O) 2 ( DMM N4py) 2 ] 3 + (2) species by H 2 O 2 oxidation of the corresponding Mn II complexes. The electronic absorption and EPR properties of 1 and 2 are nearly identical. Analysis of the EXAFS region of the Mn K-edge XAS spectra of 1 and 2 reveals comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…The complex signal of [Mn IV (O)(N3pyQ)] 2+ at g eff = 2.0 shows at least 14 lines, with a hyperfine splitting of a = 7.8 mT. A large number of hyperfine lines and the g and a values are consistent with reports for bis(μ-oxo)dimanganese(III,IV) complexes with similar ligands ( g = 2.0 and a = 7.7 mT) . Notably, bis(μ-oxo)dimanganese(III,IV) complexes have been observed as decay products of similar Mn IV -oxo species …”
Section: Results and Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The complex signal of [Mn IV (O)(N3pyQ)] 2+ at g eff = 2.0 shows at least 14 lines, with a hyperfine splitting of a = 7.8 mT. A large number of hyperfine lines and the g and a values are consistent with reports for bis(μ-oxo)dimanganese(III,IV) complexes with similar ligands ( g = 2.0 and a = 7.7 mT) . Notably, bis(μ-oxo)dimanganese(III,IV) complexes have been observed as decay products of similar Mn IV -oxo species …”
Section: Results and Analysissupporting
confidence: 89%
“…A large number of hyperfine lines and the g and a values are consistent with reports for bis(μ-oxo)dimanganese(III,IV) complexes with similar ligands (g = 2.0 and a = 7.7 mT). 61 Notably, bis(μ-oxo)dimanganese-(III,IV) complexes have been observed as decay products of similar Mn IV -oxo species. 25 The EPR spectrum of [Mn IV (O)(N4py Me2 )] 2+ shows a positive signal with prominent hyperfine splitting at g = 4.6, a derivative at g = 3.1, and negative signals at g = 1.9 and 1.6.…”
Section: ■ Results and Analysismentioning
confidence: 99%
“…, Mn–O distance 1.80–1.94 Å, Mn⋯Mn distance 2.59–2.91 Å, and bond angle of Mn–O–Mn ranging between 92.5 and 102.3°). 40 The distances of ligands bound to Mn( iii ) were Mn1–O5 1 1.841(4) Å, Mn1–N1 2.116(4) Å, Mn1–N2 2.089(2) Å, and Mn1–N5 2.075(4) Å. The short metal–metal distance together with appropriately short Mn( iii )–O bond lengths indicate the existence of a diamond core at the center.…”
Section: Resultsmentioning
confidence: 96%
“…Several studies have recently shown that just like their Fe IV O analogues nonheme Mn IV -oxo compounds supported by neutral pentadentate ligands also activate strong C–H bonds. , It has been suggested that the enhanced hydrogen atom abstraction (HAT) reactivity of these Mn IV O species originate from the synergistic effects of two-level reactivity involving the 4 B 1 and 4 E levels electronic states, the π-bonding interactions of substrates with the Mn IV O group, and the unusually high redox potential of the Mn III/IV couple . Interestingly, the HAT reactivity was not limited to mononuclear compounds but also observed for some dinuclear complexes . Furthermore, the presence of terminal oxo ligands is not even a prerequisite for manganese­(IV) species to exhibit biomimetic catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…9 Interestingly, the HAT reactivity was not limited to mononuclear compounds but also observed for some dinuclear complexes. 10 ligands is not even a prerequisite for manganese(IV) species to exhibit biomimetic catalytic activity. 11 One notable series of such compounds are the radical-supported Mn IV 2 (L • ) 2 (L •• ) and Mn IV L(L • ) 2 where L are o-aminophenols derived from aniline and m-phenylenediamine, which catalyze the oxidation of catechol to quinone and the oxidative coupling of C−C bonds of hindered phenols using oxygen as the sole oxidant.…”
Section: ■ Introductionmentioning
confidence: 99%